Fungi mediated production and practical purification of (R)-(-)-3-quinuclidinol - Kolet, Swati P.; Jadhav, Dipesh D.; Priyadarshini, Balaraman; Swarge, Bhagyashree N.; Thulasiram, Hirekodathakallu V. (Tetrahedron Letters, 2014)
A fungal system belonging to Mucoraceae family (Mucor piriformis) was explored for the asymmetric reduction of a prochiral ketone, 3-quinuclidinone (I) in an efficient manner to produce an important pharmaceutical precursor (R)-(-)-3-quinuclidinol (II) with similar to 96% enantiomeric excess. The efficiency of the process was improved by developing a cation exchange resin (Amberlite IR-120) which assisted the purification of water soluble metabolite II from fermentation media. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: (R)-(-)-3-Quinuclidinol; Amberlite IR-120; Biotransformation; Ion exchange resin; Mucor pinformis

Lipase mediated separation of triterpene structural isomers, alpha- and beta-amyrin - Haldar, Saikat; Kale, Balaji S.; Jadhav, Dipesh D.; Thulasiram, Hirekodathakallu V. (Tetrahedron Letters, 2014)
Pentacyclic triterpenoids alpha- and beta-amyrin possess a wide range of biological and pharmacological activities. High structural similarity between these two structural isomers makes their chromatographic separation an ineffective and tedious choice. In this study, Candida rugosa lipase catalyzed separation protocol for the isolation of individual isomers has been developed. In the presence of vinyl acetate as the acyl donor, Candida rugosa lipase carried out acetylation of beta-amyrin more efficiently as compared to alpha-amyrin leading to a kinetic separation. The conditions of transesterification reaction were optimized systematically, which was utilized to separate alpha- and beta-amyrin from a mixture obtained from the latex of Plumeria obtusa. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Amyrin; Candida rugosa; Kinetic separation; Lipase; Structural isomer

Fungal mediated kinetic resolution of racemic acetates to (R)-alcohols using fusarium proliferatum - Jadhav, Dipesh D.; Patil, Harshal S.; Chaya, Patil S.; Thulasiram, Hirekodathakallu V. (Tetrahedron Letters, 2016)
Fungal mediated kinetic resolution of seven acyclic/aromatic acetates was achieved using Fusarium proliferatum to furnish (R)-alcohols in high enantiomeric excess (>95%). The kinetic resolution was established as one-pot two-step de-esterification/oxidation biocatalytic process. Further, the preparative scale synthesis of (R)-(+)-1-phenylethanol was accomplished through de-esterification/oxidation of (+/-)-1-phenylethyl acetate using the whole cell of F. proliferatum NCIM 1105. (C) 2016 Elsevier Ltd. All rights reserved.

Oral feeding with polyunsaturated fatty acids fosters hematopoiesis and thrombopoiesis in healthy and bone marrow-transplanted mice - Limbkar, Kedar; Dhenge, Ankita; Jadhav, Dipesh D.; Thulasiram, Hirekodathakallu V.; Kale, Vaijayanti; Limaye, Lalita (Journal of Nutritional Biochemistry, 2017)
Hematopoietic stem cells play the vital role of maintaining appropriate levels of cells in blood. Therefore, regulation of their fate is essential for their effective therapeutic use. Here we report the role of polyunsaturated fatty acids (PUFAs) in regulating hematopoiesis which has not been explored well so far. Mice were fed daily for 10 days with n-6/n-3 PUFAs, viz. linoleic acid (LA), arachidonic acid (AA), alpha-linolenic acid and docosahexanoic acid (DHA) in four separate test groups with phosphate-buffered saline fed mice as control set. The bone marrow cells of PUFA-fed mice showed a significantly higher hematopoiesis as assessed using side population, Lin-Sca-1(+)ckit+, colony-forming unit (CFU), long-term culture, CFU-spleen assay and engraftment potential as compared to the control set. Thrombopoiesis was also stimulated in PUFA-fed mice. A combination of DHA and AA was found to be more effective than when either was fed individually. Higher incorporation of PUFAs as well as products of their metabolism was observed in the bone marrow cells of PUFA-fed mice. A stimulation of the Wnt, CXCR4 and Notch1 pathways was observed in PUFA-fed mice. The clinical relevance of this study was evident when bone marrow-transplanted recipient mice, which were fed with PUFAs, showed higher engraftment of donor cells, suggesting that the bone marrow microenvironment may also be stimulated by feeding with PUFAs. These data indicate that oral administration of PUFAs in mice stimulates hematopoiesis and thrombopoiesis and could serve as a valuable supplemental therapy in situations of hematopoietic failure. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Bone Marrow Transplantation (Bmt); Cord Blood; Down-regulation; Ex-vivo Expansion; Hematopoiesis; Hematopoietic Stem Cells (Hscs); Lipid rafts; Myocardial-infarction; Polyunsaturated Fatty Acids; Progenitor Cells; Prostaglandin-e2; Self-renewal; Spleen Colonies; Stem-cell Proliferation; Thrombopoiesis

Regioselective and efficient enzymatic synthesis of antimicrobial andrographolide derivatives - Patil, Harshal S.; Jadhav, Dipesh D.; Paul, Ajay; Mulani, Fayaj A.; Karegaonkar, Shrikant J.; Thulasiram, Hirekodathakallu V. (Bioorganic & Medicinal Chemistry Letters, 2018)
Labdane diterpene andrographolide (1) is a major constituent of Andrographis paniculata and known to exhibit wide spectrum of biological activities. In this study, regioselective monoesters of (1) have been synthesized by using Amano lipase AK (Pseudomonas fluorescens) as a biocatalyst. Amano lipase AK was able to execute highly efficient esterification of hydroxyl group attached to C-14 carbon of (1) in presence of acyl donors. Among the various synthesized derivatives including two novel compounds such as andrographolide-14-propionate (3) and andrographolide-14-caproate (5) displayed antimicrobial activity against Staphylococcus aureus with low minimal inhibitory concentration (MIC) 4 mu g/mL and 16 mu g/mL respectively. Furthermore, they have shown low hemolysis activity at their respective MIC and increase in the permeability of the bacterial cell membrane as delineated by FITC uptake and SEM imaging studies. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Acylation; Andrographolide; Antimicrobial activity; biocatalysis; Hemolysis; Lipase; Natural product